2017
DOI: 10.1039/c7ra00473g
|View full text |Cite
|
Sign up to set email alerts
|

Rapid identification of dual p53-MDM2/MDMX interaction inhibitors through virtual screening and hit-based substructure search

Abstract: Multi-target agents have garnered great interest over the past decade for their favorable therapeutic efficacy and drug resistance profiles. Recently, dual inhibition of the p53 tumor suppressor interaction with its two negative regulators MDM2 and MDMX has become an attractive anticancer approach as it can induce sustained MDM2/MDMX antagonism and robust p53 activation. However, small molecule inhibitors with dual specificity against MDM2 and MDMX are difficult to design and are still scarce. To identify nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…19A). [115][116][117][118][119][120] After decades of development, the interaction of p53-MDM2/MDMX has been well studied, which provides a good platform to verify the effectiveness of helical unnatural mimics.…”
Section: Peptoids the Peptoids Also Show Resistance To Proteolysis An...mentioning
confidence: 99%
“…19A). [115][116][117][118][119][120] After decades of development, the interaction of p53-MDM2/MDMX has been well studied, which provides a good platform to verify the effectiveness of helical unnatural mimics.…”
Section: Peptoids the Peptoids Also Show Resistance To Proteolysis An...mentioning
confidence: 99%
“…Furthermore, VIP116 with PEG-Stabilized Lipodisks promotes p53-mediated apoptosis with increasing peptide accumulation and decreasing toxicity [40]. Other dual MDM2 and MDMX inhibitors are being developed with significant anticancer activities in preclinical studies, including RO-2443 and optimized RO-5963 [41,42].…”
Section: Development Of Drugs To Restore the Activities Of Wtp53 By T...mentioning
confidence: 99%
“…MDM2/X dual inhibitors have been reviewed elsewhere ( 37 , 103 ). In a study by Chen et al, NSC623731 was identified as the most potent dual specificity inhibitor via virtual screening and computational models and demonstrated anti-proliferative activity on the U87MG p53 wt GB cell line ( 171 ). In combined treatment strategies dual MDM2/X inhibitor RS3594 and CXCRX inhibition presented synergic effects against GB pre-clinically ( 178 ).…”
Section: Current Status Of Mdm2/x Inhibition and P53 Activation For The Treatment Of Gbmentioning
confidence: 99%